Preparation method and application of modified titanium dioxide nanoparticles
By adding TiO2 nano-microsphere powder and other additives to the WO3 precursor solution, the TiO2/WO3 nanocomposite particles are formed, which solves the problem of insufficient bonding between WO3 and TiO2, improves the photocatalytic efficiency and light absorption performance, and is suitable for photogenerating cathodes Preparation of anticorrosion coatings.
Patent Information
- Application Number
- CN202411413380.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
When using WO3 to modify TiO2, the interface bond between the two is weak, resulting in the photogenerated carriers being easily recombined, affecting the photocatalytic efficiency.
By adding anatase TiO2 nano-microsphere powder, sodium hexametaphosphate and oxalic acid dihydrate to the precursor solution of WO3, ultrasonic dispersion and mechanical stirring, followed by hydrothermal reaction to form TiO2/WO3 nanocomposite particles, strengthening Interface combination.
It significantly improves the separation efficiency of photogenerated carriers, expands the light absorption band to 476nm, and improves photocatalytic performance. It is suitable for photoanode fillers for the preparation of photogenerated cathode anticorrosion coatings.
Smart Images

Figure CN119286298A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material synthesis, and in particular to a preparation method of modified titanium dioxide nanoparticles and application thereof. Background Art
[0002] At present, stainless steel, aluminum alloy and other metal components used in ships and marine engineering equipment in the marine environment are facing strong ultraviolet rays, high salt fog, and high humidity and heat in the service environment, and are prone to failure due to rust. Applying coatings on the surface of metal components by brushing, spraying, etc. has always been the mainstream anti-corrosion method. In recent years, the development of smart coatings is in the ascendant, and gratifying research progress has been made in the directions of light response, pH response, and mechanical response. Among them, photogenerated cathodic anti-corrosion coatings can make full use of the radiation of sunlight in the marine environment, convert it into electrical energy, and perform cathodic protection on metals. It is a green anti-corrosion technology.
[0003] Since the discovery of the photocatalytic properties of TiO2 in 1972, it has become the main research material in the field of photocatalysis due to its low price and wide availability. However, when TiO2 is used in photocathode protective coating systems, it also has the following disadvantages: (1) the inhomogeneity or defects of TiO2; (2) the light absorption threshold of TiO2 is small and it can only absorb ultraviolet light; (3) the photoelectric conversion efficiency is low; (4) the photogenerated carriers recombine too quickly and there is no photocathode protection in the dark state. Therefore, in order to broaden its light absorption range and promote the separation of photogenerated carriers, researchers have carried out a lot of research and proposed many modification and modification methods, such as: element doping, sensitization, morphology control, heterostructure construction, carbon material modification, etc. CN106555188A doped Ag into TiO2 nanotubes to broaden its light absorption range. CN108751168A prepared flower-shaped rhombus TiO2 to improve its utilization of visible light. The antimony-based composite sensitized TiO2 composite film in CN109207969A expanded its visible light absorption band to 600-700nm. CN109735847A, CN107723712A and CN110106508A constructed heterojunctions of AgInS2, ZnIn2S4 and Bi2O2CO3 with TiO2 to improve the separation efficiency of photogenerated carriers. CN108149227A introduced reduced graphene oxide (rGO) into the mixed powder of TiO2 and WO3 to improve the transmission rate of photogenerated electrons.
[0004] WO3 is a narrow bandgap metal oxide with good visible light absorption capacity. In addition, WO3 has excellent electron transfer and storage capacity and is a widely studied energy storage material. Using WO3 to modify and modify TiO2 can broaden the light absorption range of semiconductor particles to the visible light region. The heterojunction structure formed by the combination of the two is conducive to the separation and transfer of photogenerated carriers, and can provide cathode protection for metals in the dark state. CN117800396A uses a secondary hydrothermal method to load TiO2 on WO3 to prepare a WO3 / TiO2 composite material. CN113117665A directly loads WO3 on TiO2 powder by hydrothermal reaction. However, the above method has the problem that the two semiconductor interfaces are not tightly combined, and the photogenerated carriers are easy to recombine for the second time, which is not suitable for the preparation of photogenerated cathode coating photoanode materials. Summary of the invention
[0005] In view of this, the present invention aims to propose a preparation method of modified titanium dioxide nanoparticles and its application, so as to solve the problem that when TiO2 is modified by WO3, the interface bonding between the two is weak, which easily leads to secondary recombination of photogenerated carriers and affects the photocatalytic efficiency.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] In one aspect, the present invention provides a method for preparing modified titanium dioxide nanoparticles, comprising the following steps:
[0008] Step 1, preparation of WO3 precursor solution;
[0009] Step 2: adding anatase TiO2 nanosphere powder to the WO3 precursor solution of step 1, and adding a dispersant and oxalic acid dihydrate, followed by ultrasonic dispersion and mechanical stirring to obtain a turbid mixed solution;
[0010] Step 3: subjecting the mixed solution obtained in step 2 to a hydrothermal reaction, centrifuging to obtain a solid product, washing it three times with deionized water and ethanol in sequence, and then drying it;
[0011] Step 4: calcine the solid product obtained after drying in step 4 for 2 to 3 hours, grind it after cooling, and obtain TiO2 / WO3 nanocomposite particles.
[0012] Furthermore, in step 1, Na2WO4·2H2O, Na2SO4 and deionized water are mixed and stirred evenly to obtain a colorless and transparent solution, and then 3 mol / L dilute hydrochloric acid is added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0013] Furthermore, in step 1, the molar ratio of the added amount of Na2WO4·2H2O and Na2SO4 is 2 to 5: 1. The mass fraction of the WO3 precursor solution is 2.0 to 15.9%.
[0014] Furthermore, in step 2, the dispersant is sodium hexametaphosphate, and the mass ratio of TiO2 nanosphere powder to sodium hexametaphosphate is 40 to 50:1.
[0015] Furthermore, in step 2, the mass ratio of TiO2 nanosphere powder to oxalic acid dihydrate is 70-80:1.
[0016] Furthermore, in step three, the temperature of the hydrothermal reaction is 170-190° C., and the hydrothermal reaction time is 23-25 hours.
[0017] Furthermore, in step three, centrifuge is used for centrifugation, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 2-4 minutes, the drying temperature is 70-90° C., and the drying time is 8 hours.
[0018] Furthermore, in step 4, the calcination temperature is 300-800°C.
[0019] On the other hand, the present invention also proposes the use of TiO2 / WO3 nanocomposite particles prepared by the above-mentioned preparation method of modified titanium dioxide nanoparticles in the preparation of photocathode anti-corrosion coatings as photoanode fillers.
[0020] Compared with the prior art, the preparation method and application of modified titanium dioxide nanoparticles described in the present invention have the following advantages:
[0021] (1) The TiO2 / WO3 nanocomposite particles obtained by the present invention enhance the interface bonding between TiO2 and WO3, which helps to improve the separation efficiency of photogenerated carriers under light irradiation;
[0022] (2) The TiO2 / WO3 nanocomposite particles obtained by the present invention have good light absorption performance, the light absorption band edge is extended to 476nm, and the absorbance is significantly improved, and can be used for the preparation of photoanode fillers and photogenerated cathode anticorrosion coatings;
[0023] (3) The present invention directly grows WO3 on the surface of TiO2 in situ by a single hydrothermal method based on commercial TiO2 nanoparticles, which has the advantages of simple preparation method and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0025] Figure 1 This is a SEM spectrum of the TiO2 / WO3 nanocomposite particles of Example 4 of the present invention;
[0026] Figure 2 TEM spectrum of TiO2 / WO3 nanocomposite particles of Example 4 of the present invention;
[0027] Figure 3 The UV / visible diffuse reflection absorption spectra of the TiO2 / WO3 nanocomposite particles and pure TiO2 of Examples 1 to 7 of the present invention;
[0028] Figure 4 The UV / visible diffuse reflection absorption spectra of the TiO2 / WO3 nanocomposite particles and pure TiO2 of Examples 4 and 8 to 11 of the present invention;
[0029] Figure 5 This is the X-ray diffraction spectrum of the TiO2 / WO3 nanocomposite particles of Examples 3 to 5 of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be noted that the data in the following experimental examples are obtained by the inventor through a large number of experiments. Due to space limitations, only a part of them is shown in the specification, and those of ordinary skill in the art can understand and implement the present invention under these data. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these changes or modifications also fall within the scope protected by the present application.
[0031] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0032] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0033] A method for preparing modified titanium dioxide nanoparticles comprises the following steps:
[0034] Step 1, preparation of WO3 precursor solution;
[0035] Step 2: adding anatase TiO2 nanosphere powder to the WO3 precursor solution of step 1, and adding a dispersant and oxalic acid dihydrate, followed by ultrasonic dispersion and mechanical stirring to obtain a turbid mixed solution;
[0036] Step 3: subjecting the mixed solution obtained in step 2 to a hydrothermal reaction, centrifuging to obtain a solid product, washing it three times with deionized water and ethanol in sequence, and then drying it;
[0037] Step 4: calcine the solid product obtained after drying in step 4 for 2 to 3 hours, grind it after cooling, and obtain TiO2 / WO3 nanocomposite particles.
[0038] As a preferred example of the present invention, in step 1, Na2WO4·2H2O, Na2SO4 and deionized water are mixed and stirred evenly to obtain a colorless and transparent solution, and then 3 mol / L dilute hydrochloric acid is added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0039] In step 1, the molar ratio of the added amount of Na2WO4·2H2O and Na2SO4 is 2 to 5: 1. The mass fraction of the WO3 precursor solution is 2.0 to 15.9%.
[0040] As a preferred example of the present invention, in step 2, the dispersant is sodium hexametaphosphate. Using sodium hexametaphosphate as a dispersant can promote the dispersion of TiO2 particles, making WO4 2- The ions are uniformly adsorbed on the surface of TiO2. The oxalic acid dihydrate can promote the 2- Ion adsorption on the surface of TiO2. The addition of sodium hexametaphosphate and oxalic acid dihydrate enhances the interface bonding between TiO2 and WO3, making it easier to modify TiO2 using WO3, which helps to improve the separation efficiency of photogenerated carriers under light irradiation, thereby improving the photocatalytic effect.
[0041] In step 2, the mass ratio of TiO2 nanosphere powder to sodium hexametaphosphate is 40 to 50: 1. Further, the mass ratio of TiO2 nanosphere powder to sodium hexametaphosphate is 45: 1.
[0042] In step 2, the mass ratio of TiO2 nanosphere powder to oxalic acid dihydrate is 70-80: 1. Further, the mass ratio of TiO2 nanosphere powder to oxalic acid dihydrate is 76:1.
[0043] In step 2, the mass ratio of TiO2 nanosphere powder to Na2WO4·2H2O in the precursor solution of WO3 is 0.078-6.324:1.
[0044] As a preferred example of the present invention, in step three, the temperature of the hydrothermal reaction is 170-190° C., and the hydrothermal reaction time is 23-25 hours.
[0045] In step 3, centrifuge is used for centrifugation, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 2-4 minutes, the drying temperature is 70-90° C., and the drying time is 8 hours.
[0046] In step 4, the calcination temperature is 300-800° C. Further, the calcination temperature is 600-800° C.
[0047] The mass ratio of TiO2 to WO3 in the TiO2 / WO3 nanocomposite particles obtained by the preparation method of the modified titanium dioxide nanoparticles of the present invention is 1-9:1-9.
[0048] The present invention directly grows WO3 on the surface of TiO2 in situ by a primary hydrothermal method based on commercial TiO2 nanoparticles, which has the advantages of simple preparation method and low cost. Compared with pure TiO2, the prepared TiO2 / WO3 nanocomposite particles have good light absorption performance, the light absorption band edge can be extended to 476nm, and the absorbance is significantly improved. The TiO2 / WO3 nanocomposite particles prepared by the preparation method of the present invention can be used for photoanode fillers to prepare photogenerated cathode anticorrosion coatings, which is conducive to promoting the large-scale application of photogenerated cathode protection technology.
[0049] The anatase TiO2 nanosphere powder used in the following examples was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and other materials and reagents were purchased from commercial sources.
[0050] Example 1
[0051] 0.3301 g of Na2WO4·2H2O and 0.2848 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0052] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0053] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0054] The dried solid product was calcined in a muffle furnace at 300°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0055] Example 2
[0056] 0.3301 g of Na2WO4·2H2O and 0.2848 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0057] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0058] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0059] The dried solid product was calcined in a muffle furnace at 400°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0060] Example 3
[0061] 0.3301 g of Na2WO4·2H2O and 0.712 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0062] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0063] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0064] The dried solid product was calcined in a muffle furnace at 500°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0065] Example 4
[0066] 0.3301 g of Na2WO4·2H2O and 0.712 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0067] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0068] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0069] The dried solid product was calcined in a muffle furnace at 600°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0070] Example 5
[0071] 0.3301 g of Na2WO4·2H2O and 0.712 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0072] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0073] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0074] The dried solid product was calcined in a muffle furnace at 700°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0075] Example 6
[0076] 0.3301 g of Na2WO4·2H2O and 0.712 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0077] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0078] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0079] The dried solid product was calcined in a muffle furnace at 800°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0080] Example 7
[0081] 0.3301 g of Na2WO4·2H2O and 0.712 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0082] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0083] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0084] The dried solid product was calcined in a muffle furnace at 900°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 7:3.
[0085] Example 8
[0086] 0.1265 g of Na2WO4·2H2O and 0.2724 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0087] 0.8 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0178 g of sodium hexametaphosphate and 0.0106 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0088] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0089] The dried solid product was calcined in a muffle furnace at 600°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 9:1.
[0090] Example 9
[0091] 0.8537 g of Na2WO4·2H2O and 1.8381 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0092] 0.6 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0133 g of sodium hexametaphosphate and 0.0079 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0093] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 190°C for 25 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0094] The dried solid product was calcined in a muffle furnace at 600° C. for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 5:5.
[0095] Example 10
[0096] 1.7958 g of Na2WO4·2H2O and 3.8664 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then, 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0097] 0.5409 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0120 g of sodium hexametaphosphate and 0.0071 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0098] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 170°C for 23 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0099] The dried solid product was calcined in a muffle furnace at 600°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 3:7.
[0100] Embodiment 11
[0101] 1.9789 g of Na2WO4·2H2O and 4.2609 g of Na2SO4 were added to 30 mL of deionized water and stirred evenly to completely dissolve the solid powder to obtain a solution. Then 3 mol / L of dilute hydrochloric acid was added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
[0102] 0.1545 g of anatase TiO2 nanosphere powder was added to the WO3 precursor solution, and 0.0034 g of sodium hexametaphosphate and 0.0020 g of oxalic acid dihydrate were added, followed by ultrasonic dispersion for 0.5 hour and mechanical stirring for 0.5 hour to obtain a white turbid liquid.
[0103] The white turbid liquid was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor and the hydrothermal reaction was carried out at 180°C for 24 hours. The obtained product was separated by a centrifuge at a speed of 10,000 r / min, then washed twice with deionized water, and finally washed once with ethanol, and the obtained solid product was dried at 80°C for 8 hours.
[0104] The dried solid product was calcined in a muffle furnace at 600°C for 2 hours. After cooling, the solid was ground to obtain TiO2 / WO3 nanocomposite particles, with a mass ratio of TiO2 to WO3 of 1:9.
[0105] The TiO2 / WO3 nanocomposite particles prepared in Examples 1 to 11 were characterized by SEM. WO3 was uniformly loaded on TiO2, and the particle size of the composite particles was 50 nm. In view of the same morphology of Examples 1 to 11, in order to avoid redundant description, only the SEM spectrum of the TiO2 / WO3 nanocomposite particles prepared in Example 4 is shown in this application, as shown in FIG. Figure 1 shown.
[0106] The TiO2 / WO3 nanocomposite particles prepared in Examples 1 to 11 were characterized by TEM. In view of the consistency of the TEM spectra of Examples 1 to 11, in order to avoid redundancy, only the TEM spectra of the TiO2 / WO3 nanocomposite particles prepared in Example 4 are shown in this application, as shown in FIG. Figure 2 As shown. The upper part of the red dotted line contains only 0.35nm TiO2 (101) crystal plane, while the lower part of the red dotted line contains both 0.35nm TiO2 (101) crystal plane and 0.37nm WO3 (200) crystal plane, indicating that WO3 is successfully attached to the TiO2 surface and there is an obvious interface between the two at the microscopic level, that is, Figure 2 The red dotted line in the figure can form a heterojunction structure.
[0107] The TiO2 / WO3 nanocomposite particles prepared in Examples 1 to 11 were subjected to UV / visible light diffuse reflection absorption tests. Figures 3-4 The cut-off wavelength of pure TiO2 absorption is 379nm, the cut-off wavelength of the TiO2 / WO3 nanocomposite particles in Example 1 is widened to 476nm, and the absorbance at 410nm is 0.289 (au); the cut-off wavelength of the TiO2 / WO3 nanocomposite particles in Example 2 is widened to 476nm, and the absorbance at 410nm is 0.249 (au); the TiO2 / WO3 nanocomposite particles in Example 3 are widened to 476nm, and the absorbance at 410nm is 0.249 (au); 2 / The cut-off wavelength of light absorption of the WO3 nanocomposite particles is broadened to 476 nm, and the absorbance at 410 nm is 0.293 (au); the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 4 is broadened to 476 nm, and the absorbance at 410 nm is 0.423 (au); the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 5 is broadened to 476 nm, and the absorbance at 410 nm is 0.348 (au); the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 6 is broadened to 476 nm, and the absorbance at 410 nm is 0.375 (au); the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 7 is broadened to 476 nm, and the absorbance at 410 nm is 0.356 (au); Example 8 The cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles is broadened to 476 nm, and the absorbance at 410 nm is 0.110 (au). In Example 8, due to the low content of added Na2WO4·2H2O, the WO3 loaded on the composite particles is also relatively small, so the absorbance is low; the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 9 is broadened to 476 nm, and the absorbance at 410 nm is 0.430 (au); the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 10 is broadened to 476 nm, and the absorbance at 410 nm is 0.497 (au); the cut-off wavelength of light absorption of the TiO2 / WO3 nanocomposite particles of Example 11 is broadened to 476 nm, and the absorbance at 410 nm is 0.585 (au).
[0108] The TiO2 / WO3 nanocomposite particles prepared by the preparation method of the present invention can greatly increase the cutoff wavelength of light absorption. In addition to having good light absorption in the ultraviolet region, the response to visible light (400-800nm) is enhanced. And as the calcination temperature is increased to 600-800°C, such as Examples 4-6 and Examples 8-11, the visible light absorption peak is enhanced. However, as the calcination temperature is further increased, such as Example 7, when the calcination temperature is 900°C, the absorption peak in the ultraviolet region decreases. Therefore, the calcination temperature is preferably 600-800°C.
[0109] The TiO2 / WO3 nanocomposite particles prepared in Examples 1 to 11 were subjected to X-ray diffraction (XRD) testing, and diffraction peaks of anatase TiO2 and hexagonal and / or monoclinic WO3 appeared. Figure 5 Among them, Examples 3 to 5 are representative. In Example 3, in addition to the diffraction peak of anatase TiO2, the diffraction peak of WO3 meets JCPDS#43-1035 and JCPDS#33-1387, and is a mixture of hexagonal and monoclinic types. In Example 4, in addition to the diffraction peak of anatase TiO2, the diffraction peak of WO3 meets JCPDS#43-1035, and is monoclinic. In Example 5, in addition to the diffraction peak of anatase TiO2, the diffraction peak of WO3 meets JCPDS#43-1035, and is monoclinic.
[0110] The preparation method of the modified titanium dioxide nanoparticles of the present invention can obtain TiO2 / WO3 nanocomposite particles, which enhances the interface bonding between TiO2 and WO3 and helps to improve the separation efficiency of photogenerated carriers under light irradiation. It also has good light absorption performance, the light absorption band edge is extended to 476nm, and the absorbance is significantly improved, and can be used for the preparation of photoanode fillers and photogenerated cathode anticorrosion coatings.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing modified titanium dioxide nanoparticles, characterized in that: The steps include: Step 1, preparation of WO3 precursor solution; Step 2: adding anatase TiO2 nanosphere powder to the WO3 precursor solution of step 1, and adding a dispersant and oxalic acid dihydrate, followed by ultrasonic dispersion and mechanical stirring to obtain a turbid mixed solution; Step 3: subjecting the mixed solution obtained in step 2 to a hydrothermal reaction, centrifuging to obtain a solid product, washing it three times with deionized water and ethanol in sequence, and then drying it; Step 4: calcine the solid product obtained after drying in step 4 for 2 to 3 hours, grind it after cooling, and obtain TiO2 / WO3 nanocomposite particles.
2. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step 1, Na2WO4·2H2O, Na2SO4 and deionized water are mixed and stirred to obtain a colorless and transparent solution, and then 3 mol / L dilute hydrochloric acid is added dropwise to adjust the pH value of the solution to 0.5 to obtain a WO3 precursor solution.
3. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step 1, the molar ratio of the added amount of Na2WO4·2H2O and Na2SO4 is 2 to 5:
1. The mass fraction of the WO3 precursor solution is 2.0 to 15.9%.
4. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step 2, the dispersant is sodium hexametaphosphate, and the mass ratio of TiO2 nanosphere powder to sodium hexametaphosphate is 40-50:
1.
5. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step 2, the mass ratio of TiO2 nanosphere powder to oxalic acid dihydrate is 70-80:
1.
6. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step 3, the temperature of the hydrothermal reaction is 170-190° C., and the hydrothermal reaction time is 23-25 hours.
7. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step three, centrifuge is used for centrifugation, the centrifugal speed is 8000-10000 r / min, the centrifugal time is 2-4 minutes, the drying temperature is 70-90° C., and the drying time is 8 hours.
8. The method for preparing modified titanium dioxide nanoparticles according to claim 1, characterized in that: In step 4, the calcination temperature is 300-800°C.
9. Use of TiO2 / WO3 nanocomposite particles prepared by the method for preparing modified titanium dioxide nanoparticles as claimed in any one of claims 1 to 8 in preparing photocathode anticorrosion coatings as photoanode fillers.
Citation Information
Patent Citations
Method for preparing tungsten-doped anatase type nano titanium dioxide composite powder
CN101792117A
TiO2 / WO4 photocatalyst and preparation method and application thereof
CN109999793A
Layered tungsten trioxide photoelectrode material and preparation method thereof
CN110054224A
Preparation method of energy storage type tungsten trioxide / titanium dioxide coating
CN115232488A